Impulsive conditions in Parkinson's disease: A pharmacosurveillance-supported list. (September 2021) - Fusaroli, Michele; Raschi, Emanuel; Contin, Manuela; Sambati, Luisa; Menchetti, Marco; Fioritti, Angelo; Poluzzi, Elisabetta
Abstract: Background: "Impulse Control Disorders" are behavioral conditions (e.g., gambling, hypersexuality), which are increasingly reported as reactions to dopamine agonists in Parkinson's disease. The Questionnaire for Impulsive-Compulsive Disorders in Parkinson's disease focuses only on 6 behaviors. Nonetheless, impulsivity could affect the entire range of human practices. Because of their heterogeneity and undefined boundaries, it is not clear what conditions should be considered as Impulse Control Disorders. This results in poorly standardized scientific literature and underdiagnosis. Objective: We aimed to create a comprehensive list of possible manifestations of drug-induced Impulse Control Disorders in Parkinson's disease and test it on pharmacosurveillance data. Methods: PubMed was used to identify reviews in English about Impulse Control Disorders in Parkinson's disease. Mentioned conditions were charted and translated to the lexicon of MedDRA, ICD-11, and DSM-5. The relevant MedDRA terms were used to test potential association with dopamine agonists on the FDA Adverse Event Reporting System. Results: 50 reviews published between 2001 and 2020 were identified. 66 conditions were collected as possible Impulse Control Disorders. Pathological gambling, shopping, eating and sexuality, dopamine dysregulation syndrome, hobbyism and punding were the most frequently mentioned, together with leisure activities, body-focused compulsivity, disruptive, impulse control and conduct disorders, and substance abuse. All these conditions were disproportionately reported with dopamine agonists, except for substance abuse. Conclusions: We defined a potential extended list of ICDs, which, along with its conversion to international taxonomies, can support the identification of drug-induced conditions in pharmacovigilance archives, as well as monitoring processes in clinical practice. Highlights: Impulse Control Disorders are behavioural addictions induced by dopamine agonists. Their unclear boundaries can result in delayed diagnosis and unknown prevalence. An extended list was defined by gathering relevant reviews from the literature. A list of Impulse Control Disorder was built using MedDRA, ICD-11 and DSM-5. Association with dopamine agonists was supported by pharmacovigilance.